Antimicrobial activity of garlic-tetracycline combination. - Ninal, Josine L
Serial twofold concentrations of garlic and tetracycline were prepared and tested against three organisms to determine their individual minimum inhibitory concentrations (MIC). Their combination effect was also determined based on their MIC's., Garlic extract inhibited Escherichia coli growth with a least concentration of 4.0 Pseudomonas aeroginosa at 4.0 and Staphylococcus aureus at 2.0. The minimum inhibitory concentration of tetracycline for all test organisms was recorded at 16ug/ml. Antagonism was observed of the interaction between the two antimicrobials, with a fractional inhibitory concentration (FIC) index value equal to 2.0 for each of the three test organisms (based on equipotent concentrations), with ranges from 1.0-2.042 for Escherichia coli, 1.0-2.125 for Pseudomonas aeroginosa, and 1.0-2.208 for Staphylococcus aureus.